Learner Autonomy: EFL Teachers’ View - Aziza Rahimjonova (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
Learner autonomy is a critical concept in language education, emphasizing students' responsibility for their own learning and having with modern educational goals of fostering critical thinking, problem-solving, and lifelong learning. This study explores teachers' perspectives on learner autonomy, examining their understanding, strategies, and challenges in its implementation. The findings underscore the pivotal role of teachers in bridging the gap between theoretical principles and classroom application, ensuring that learner autonomy becomes a sustainable element of language education